East Africa digital grain hub system brings farming costs down - Rutto, Samwel (Technical Centre for Agricultural and Rural Cooperation, 2018)
Samwel Rutto, Regional Manager (Structured Trading Systems) at the Eastern Africa Grain Council (EAGC), explains how the Grain Hub System is helping farmers reduce costs.